Wheat Phenological Development and Growth Studies As Affected by Drought and Late Season High Temperature Stress under Arid Environment - Ihsan, Muhammad Z.; El-Nakhlawy, Fathy S.; Ismail, Saleh M.; Fahad, Shah; daur, Ihsanullah (Frontiers in Plant Science, 2016)
Crop phenological development study evaluates the potential for adaptability and tolerance of genotypes to arid environment. Present study examined the effect of drought stress (100%, 75% and 50% FC), planting times (16-November, 01-December, 16-December and 01-January) and genotypes (Yocoro Rojo, FKAU-10, Faisalabad-08 and Galaxy L-7096) on phenological development, growth indices, grain yield and water use efficiency of drip-irrigated wheat. Development of wheat genotypes were measured at five phenological growth stages (tillering, jointing, booting, heading and maturity) and correlation of growth indices (30, 45, 60 and 75 DAS) were also estimated against final grain yield. Phenological development study measured early tillering in drought stressed plots, while at maximum, 31 days were taken to complete tillering stage. Days to complete 50% heading and physiological crop maturity were the most susceptible growth stages that resulted in a reduction of 31-72% in number of days to complete these growth stages. Wheat genotypes grown with 50% FC reported the shortest grain filling duration. The genotype, Fsd-08 presented greater adaptability to studied arid climate and recorded 31%, 35% and 38% longer grain filling period as compared with rest of the genotypes at 100-50% FC respectively. December sowing mitigated the drought and delayed plantation effects by producing superior growth and yield (2162 kg ha-1) at severe drought stress. The genotype Fsd-08 and L-7096 recorded the minimum plant height (36 cm) and the shortest growth cycle (76 days) for January plantation with 50% FC. At severe drought stress leaf area index, dry matter accumulation, crop growth rate and net assimilation rate were decreased by 67%, 57%, 34% and 38% as compared to non-stressed plots. The genotype, Fsd-08 and F-10 were the superior one and secured 14-17% higher grain yield as compared to local YR for severely stressed plots. The correlation between crop growth indices and grain yield depicted the highest value (0.58-0.71) at 60-75 DAS. So the major contribution of these growth indices towards grain yield was at the start of reproductive phase. It’s clear that booting and grain filing are the most sensitive growth stages that are severely affected by both, drought and delay in plantation.